Contributions of piezoelectricity and triboelectricity to a hydroxyapatite/PVDF–HFP fiber-film nanogenerator. (January 2023) - Wang, Shengqian; Tong, Wangshu; Li, Yanan; Zhang, Panpan; Liu, Yulun; Chen, Yiyuan; Zhang, Yihe
Abstract: Poly(vinylidene fluoride) (PVDF)-based piezoelectric nanogenerators (PENGs), which are prepared by electrospinning, are widely used in self-powered field owing to their exceptional generation performance. The generation performance of fiber PENG is usually attributed to piezoelectric effect, but the effect of triboelectricity generated among the fibers on the generation performance is not negligible. On the other hand, quantifying triboelectricity and piezoelectricity and revealing the mechanism of triboelectric–piezoelectric synergy to enhance the generation performance are urgent issues of concern. In this study, hydroxyapatite (HAP) was added into PVDF–hexafluoropropylene (HFP) as a filler to prepare nanofiber films by electrospinning. Compared with a pure PVDF–HFP nanofiber film, the generation performance of a 25 wt% HAP/PVDF–HFP nanofiber film improved from 0.2 to 1.1 V. The HAP enhancement effect was verified by HAP-content experiment and work-function measurement. The contributions of triboelectricity and piezoelectricity were 62.5% and 37.5%, respectively, calculated using the thermal-treatment experimental results. Finally, the ultraviolet photoelectron-spectrum method and model analysis revealed the synergistic effect of triboelectricity and piezoelectricity. This work employed the thermal-treatment method to quantify the contributions of triboelectricity and piezoelectricity while providing an insight into the design of PVDF fiber PENG to further enhances the generation performance. Graphical Abstract: ga1 Highlights: The addition of HAP had a positive effect on the enhancement of triboelectricity generation. Thermal-treatment method can control triboelectricity to quantify the contribution of triboelectricity and piezoelectricity. The contributions of triboelectricity and piezoelectricity in HAP/PVDF-HFP fiber-film nanogenerator were 62.5% and 37.5%. The piezoelectric field can modulate the direction of triboelectricity generation to achieve synergistic output.